UNPACKING SUCCESS AND FAILURE IN SELF-PACED EXTENSION LEARNING: A QUALITATIVE STUDY OF EFL STUDENTS' EXPERIENCES - Avilanofa Bagus Budi; Slamet Asari (University of Kuningan, 2026)
Self-Paced Extension Learning (SPEL) is increasingly adopted in secondary EFL classrooms to personalize instruction and foster learner autonomy. However, prior research has largely emphasized learning outcomes, offering limited insight into the self-regulatory and affective-cognitive processes shaping learner engagement. This study addresses this gap by exploring learners’ experiences within SPEL through the lens of Pintrich’s self-regulated learning (SRL) framework. Specifically, the study is guided by two research questions: (1) How does SPEL influence learners’ affective-cognitive engagement and SRL processes? and (2) How do individual differences and contextual factors mediate learner success and struggle in SPEL? Using a phenomenological-narrative qualitative design, data were collected from 36 lower-secondary EFL students through interviews, focus groups, reflection journals, and LMS artifacts. Data were analyzed using thematic analysis with a hybrid approach—deductive coding based on Pintrich’s SRL phases and inductive coding for emergent themes. Findings indicate that SPEL activates all SRL phases, but engagement varies significantly. Learners who set feedback-driven goals, managed pacing, and adapted strategies demonstrated higher motivation and agency, whereas others experienced anxiety, cognitive overload, and task avoidance. Digital literacy and instructional support emerged as key mediating factors. These findings contribute to a process-oriented